Opioid prescribing in the U.S. Military Health System, 2014 to 2018: fewer prescriptions, fewer pills, and shorter treatment duration. Issue 1 (January 2022) - Goldman, Ashton H.; Johnson, Daniel D.; Griffis, Clare E.; Land, Vaughn; Balazs, George C.
Abstract : Abstract: Prescription opioids remain an important driver of the opioid crisis in the United States. The purpose of this study was to examine recent changes in opioid prescribing patterns in the Military Health System (MHS) which is a nationwide health system service active duty military personnel and civilian beneficiaries. All patients prescribed opioid analgesics by MHS providers and filled at MHS pharmacies between 2014 and 2018 were identified. Prescriptions were converted to oral morphine equivalents (OMEs) and categorized based on prescribing specialty and formulation. Total opioid prescription counts and opioid prescription counts weighted by the annual number of outpatient encounters for each specialty were calculated, as were total OMEs and daily OMEs per prescription. A total of 3, 427, 308 prescriptions were included. Primary care providers and surgeons wrote 47% and 29% of opioid prescriptions, respectively. Over the study period, there was a 56% decline in annual opioid prescriptions, 25% decline in median total OMEs, and a 57% decline in opioid prescriptions per patient encounter. The proportion of prescriptions written for >90 OMEs per day declined 21%. Declines in opioid prescriptions and quantities were observed in nearly all specialties over the study period. The results of this study suggest a broad-based shift towards less opioid prescribing. Abstract : Supplemental Digital Content is Available in the Text.